ORGANIZATIONAL SILENCE AND ITS IMPACT ON A LOW LEVEL OF JOB PERFORMANCE - Hameed Alsady, Soulaf Abdalqadir (The journal of contemporary issues in business and government, 2024)
The study aimed to identify the relationship between organizational silence in its three dimensions (defensive silence, acquiescent silence, and social silence). This study was conducted on a random sample in the Commercial Bank of Iraq in Maysan Governorate and to identify the extent of the existence of a significant relationship between organizational silence and the level of performance. Occupational: Questionnaire forms were distributed to a sample of bank employees on the assumption that the community was homogeneous. Then the appropriate sample was drawn, where (80) questionnaire forms were distributed to a sample of employees, where it was found that there was a significant correlation between each dimension of organizational silence. (combined and individually) represented by (defensive silence, submissive silence, social silence) and the level of job performance.